2010
DOI: 10.5694/j.1326-5377.2010.tb03820.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential implications of genomic medicine in general practice

Abstract: Genomic research can link specific molecular genetic information with specific diseases. Implications of genomic medicine in general practice include developments in screening and diagnosis, predicting disease prognosis, and optimising preventive and therapeutic care. As users or co‐producers of genomic information, or as collaborators in genomic research, general practitioners can help realise the potential of advances in genomic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Strikingly, most GPs acknowledged lacking awareness of the clinical relevance of genomics, the 100KGP, and the NHS plans to roll out genomics. GP1’s use of the ‘ivory tower’ analogy is emblematic of GPs’ felt distance from genomic medicine and its application to their clinical practice (Sullivan et al, 2010). The quote also illustrates the policy sphere's selective approach to engaging with HCPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strikingly, most GPs acknowledged lacking awareness of the clinical relevance of genomics, the 100KGP, and the NHS plans to roll out genomics. GP1’s use of the ‘ivory tower’ analogy is emblematic of GPs’ felt distance from genomic medicine and its application to their clinical practice (Sullivan et al, 2010). The quote also illustrates the policy sphere's selective approach to engaging with HCPs.…”
Section: Resultsmentioning
confidence: 99%
“…However, GPs have increasingly become the first contact for patients wishing to access genetic services. They also now act as co‐producers of genomic information by collaborating in or recruiting patients for genomic research (Sullivan et al, 2010). Despite playing such a critical role, a small number of studies have indicated GPs’ knowledge of genetic and genomic technologies remains ‘low’ (Smit et al, 2019), with research revealing a ‘lack of confidence’ to discuss genomics with their patients (Caroll et al, 2016; Smit et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, it is logical that GPs who are motivated to start using the tools of genomic medicine, such as profiling risk for common complex disorders, and personalized medicine, recognize the need for assistance from adequately trained genetic health professionals to help facilitate best practice protocols, maximize patient care and compliance, and minimize medico-legal risk (Elwyn et al 2005;Metcalfe et al 2009b;Liaw 2010;Waxler et al 2012). It has been well recognized that, in Australia, a multidisciplinary team approach will be paramount in delivery of optimal genomic healthcare services at the primary care level (Liaw 2010;Sullivan et al 2010). Genetic counselors are not only adequately trained and experienced in adopting new genetic technologies, but they also have a critical awareness of the psychosocial implications and importance of appropriate informed consent processes that will prepare the patient for potentially complex results, and can provide follow up education and support to patients and health professionals as needed (O'Daniel 2010;Hooker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, primary care physicians (known as General Practitioners or GPs in Australasia) 1 recognize that appropriate counseling for informed consent for genetic tests and discussion of complex genetic issues requires specialized skill and a significant investment of time, in an already time poor work day. They have indicated that they do not want to be the 'gene gnomes' researching and interpreting enormous volumes of updated genetic information on a regular basis (Sullivan et al 2010;Liaw 2010;Kappagoda 2013).…”
Section: Introductionmentioning
confidence: 99%